Kebijakan Hukum Pidana Pencucian Uang Menurut Undang-Undang Nomor 8 Tahun 2010 Tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang - Anugerah Debryansyah Putera, Pujiyono*), Eko Soponyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Money laundering is a crime that seems to be making money or treasure the result of a criminal offense or illegitimate money made as if money or possessions that looks legitimate and lawful. Money laundering known first time when Al Capone a mafia in the United States that conceals the money of a deed unauthorized placed in a laundry companies. Since then known criminal act of money laundering. In 1988, Vienna Convention was held about the eradication of narcotics trade which then leads to money laundering. After that, the money laundering arrangements in the world was started and in 2002, Indonesia bore legal products about eradication criminal act money laundering namely Law of the Republic of Indonesia Number 15 Year 2002 Regarding the Crime of Money Laundering as replaced with Law of the Republic Indonesia Number 25 Year 2003.This journal going to talk about policy criminal law of money laundering according to regulation that is now used namely Law of the Republic of Indonesia Number 8 Year 2010 Regarding Countermeasure and Eradication of Money Laundering. It also compare with Malaysia’s Anti Money Laundering Act Number 2011 with a purpose to adopt a few things that do not exist in the current regulation to which it should be.Based on the research, there are several factors that still must be repaired in policy on this legal normative to be able to address money laundering in Indonesia especially in matters of a criminal offense, criminal liability and punishments. Law enforcements of money laundering using normative law still contained some weakness and should be changes in order to tackle money laundering and obtain the maximum results in the eradication of money laundering. Keyword : money laundry ,law